Recognizing Friendly Preprint Servers and Indexation: SSRN First Look and Google Scholar Data base for Novice Researchers - Radiana, Sonia Permata; Lee, Kenan; Yandra, Alexander; Filtri, Heleni; Supasa, Aprilia Yunda (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
In the era of Industry 4.0, marked by rapid technological advancements, the use of technology in academic disciplines is crucial. A significant aspect of this tech revolution is the rise of web-based preprint services and index databases, offering a direct avenue for researchers to share work without traditional peer review. This study investigates the adoption of preprint-based publication systems in Indonesian research, focusing on SSRN First Look and Google Scholar (GS) from novices researchers’ perspective in 3 based themes e.g., Benefit, Awareness, and Expectation. SSRN First Look has been vital in promoting open science, serving as a repository for diverse scientific documents. It excels in quickly and transparently disseminating research, especially beneficial for novice researchers. The research reveals the impact of SSRN First Look in facilitating the rapid sharing of research globally, including Indonesia. As an emerging force in open science, it has attracted substantial attention, underlining the growing role of preprint servers in modern academia. This survey intentionally invited 77 novice researchers who participated in a publication workshop affiliated with SSRN First Look and GS. The findings emphasize the positive impact of these platforms on the academic community, particularly novice researchers. As we advance further into the digital era, the role of preprint servers in accelerating research dissemination and promoting open scientific communication is indispensable.